The real effects of bank distress: Evidence from bank bailouts in Germany - Johannes Bersch; Hans Degryse; Thomas Kick; Ingrid Stein (Deutsche Bundesbank, 2019)
How does bank distress impact their customers' probability of default and trade credit availability? We address this question by looking at a unique sample of German firms from 2000 to 2011. We follow their firm-bank relationships through times of distress and crisis, featuring the different transmission of bank distress shocks into already weakened firm balance sheets. We find that a distressed bank bailout, which is subject to restructuring and deleveraging conditions, leads to a bank-induced increase of firms' probabilities of default. Moreover, bailouts tend to reduce trade credit availability and ultimately firms' sales. We further find that the direction and magnitude of the effects depends on firm quality and the relationship orientation of banks.
Keywords: G01; G21; G24; G33; 330; bank distress; bank risk channel; firm risk channel; relationship banking; firmdefaults; financial crisis